The rose and the beast : fairy tales retold - Block, Francesca Lia. (New York : Joanna Cotler Books/HarperCollins, 2001)
Nine classic fairy tales set in modern, magical landscapes and retold with a twist.
Snow -- Tiny -- Glass -- Charm -- Wolf -- Rose -- Bones -- Beast -- Ice.
School Library Journal
Wilson's Junior High School
Wilson's Senior High School
Book Links (A.L.A.), July 2008
Book Report, March 2001
Books for the Teen Age (NYPL), April 2001
Keywords: Fairy tales; Short stories; Fairy tales; Short stories